Renoprotective effects of antioxidants against cisplatin nephrotoxicity - Hajian Shabnam; Rafieian-Kopaei Mahmoud; Nasri Hamid (Society of Diabetic Nephropathy Prevention, 2014)
Nephrotoxicity is the major limitation for the clinical use of cisplatin as an anti-tumoural drug. Intracellular effects of cisplatin cause tubular damage and tubular dysfunction with sodium, potassium, and magnesium wasting. Renoperotective strategies against cisplatin are classified on 8 targets: 1) Decrease of cisplatin uptake by renal cell, 2) Inhibition of cisplatin metabolism, 3) Blocking cell death pathways, 4) Cyclin-dependent kinase inhibitors, 5) Pharmacologic, molecular, and genetic blockade of p53, 6) Inhibition of specific Mitogen-activated protein kinase, 7) Antioxidants usage for renoprotection against cisplatin injury and inhibit of oxidative stress, 8) Suppress of inflammation. The oxidation reactions can produce free radicals, which start chain reactions and subsequently can cause a large number of diseases in humans. Antioxidant from natural products have attracted the physicians' attentions, nowadays. The natural product antioxidants detoxify reactive oxygen species (ROS) in kidneys, without affecting the anticancer efficacy of cisplatin. Hence, antioxidants have potential therapeutic applications.